NEEDS ANALYSIS FOR THE DEVELOPMENT OF ARDUINO MICROCONTROLLER-BASED HOOKE'S LAW TEACHING TOOL GUIDEBOOK - Ayub, Yenni Novita Lestari; Setiawan, Iwan; Wardana, Rendy Wikrama (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
This research is a type of research and development (R & D) which has a focus on the goal of producing a product and testing its effectiveness and feasibility. This research model adopts the 4D research model with stages namely Define , Design , Develop , and Disseminate . This needs analysis aims to determine what teaching materials are needed on Hooke's Law material at SMA Negeri 1 Bengkulu Tengah. The research was carried out in October 2022. The research sample consisted of 40 students who were in class XI. The research instruments were interviews and student response questionnaires consisting of 18 question items regarding the need for a Hooke's Law visual aids guidebook based on the Arduino microcontroller which contained 4 aspects, namely aspects of student and teacher needs, aspects of the need for teaching materials, aspects of learning media, and aspects of interest/motivation . The results showed that most of the students were interested in developing an Arduino-based Hooke's law teaching aid guidebook.